2010
DOI: 10.1097/01.npr.0000388900.49604.e1
|View full text |Cite
|
Sign up to set email alerts
|

Men's knowledge of the human papillomavirus vaccine

Abstract: The FDA recently approved the use of the HPV quadrivalent vaccine, Gardasil, for the prevention of genital warts in males ages 9 through 26. This literature review seeks to examine men's knowledge of and interest in HPV vaccination as this could potentially affect vaccine uptake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 22 publications
1
17
0
Order By: Relevance
“…Some studies have demonstrated that an increase in knowledge regarding HPV is tied to men's intentions to reduce the number of sexual partners, use a condom during sex, and be vaccinated against HPV (Nandwani, 2010). Men do not generally perceive themselves to be susceptible to HPV and have indicated they have a lower perception of risk for contracting sexually transmitted infections (STIs) in risky sexual situations (Mehrotra, Noar, Zimmerman, & Palmgreen, 2009).…”
Section: Literature Review Knowledge About Hpv In Msmmentioning
confidence: 98%
See 1 more Smart Citation
“…Some studies have demonstrated that an increase in knowledge regarding HPV is tied to men's intentions to reduce the number of sexual partners, use a condom during sex, and be vaccinated against HPV (Nandwani, 2010). Men do not generally perceive themselves to be susceptible to HPV and have indicated they have a lower perception of risk for contracting sexually transmitted infections (STIs) in risky sexual situations (Mehrotra, Noar, Zimmerman, & Palmgreen, 2009).…”
Section: Literature Review Knowledge About Hpv In Msmmentioning
confidence: 98%
“…HPV is one of the most highly transmissible sexual diseases of this century (Nandwani, 2010;Sandfort & Pleasant, 2009). In the United States, men and women have a 75% chance of acquiring HPV within their lifetimes (Jones & Cook, 2008).…”
Section: Literature Review Knowledge About Hpv In Msmmentioning
confidence: 98%
“…Quadrivalent HPV vaccines were first approved by the American Food and Drug Administration (FDA) in 2006 and it was recommended to vaccinate girls aged 9-26 years and young women. In 2009, the use of quadrivalent vaccines in males in the same age group was approved to prevent genital warts (Rambout et al, 2007;Nandwani, 2010 been put on sale (Durusoy et al, 2010). Being accepted by the target population is essential for a vaccine to reach it (Breitkopf et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Primary protection against HPV includes elimination of the sexual risk factors and prophylactic vaccination (Nandwani, 2010). Two types of HPV vaccine are available: quadrivalent and bivalent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation